Kajian Keuntungan Usaha Ayam Broiler Pola Kemitraan Di Kecamatan 2 X 11 Kayu Tanam Kabupaten Padang Pariaman - Syafril Syafril; Ika Desma Yanti (Universitas Andalas, 2006)
The objectives of this research were to evaluate the biological and economic performances in relation to farm sizes of broiler farms which participated under nucleus-plasma scheme program. The study was conducted through field survey to collect data from farmers in 2 x 11 Kayu Tanam District, Padang Pariaman Regency from December 2004 to January 2005. Twenty broiler farmers, members of the nucleus-plasma scheme of PT. Fajar Makmur Utama, were selected by stratified random sampling method as respondents. The farmers were divided into 2 groups based on number of broiler kept i.e., strata 1 which had < 10.000 broilers and strata II  10.000 boilers. Data collected included: farm size, farming practices, mortality rate, final body weigh, marketing aspects, production cost and revenues. The data were calculated to find out revenue-cost (C-R) ratio and profitability rate. Results showed that mortality and final body weigh were not significantly affected by farm size, but economic performances in terms of RC ratio and profitability rate were found better by the higher farm size. RC ratio of farms of strata I was 1.34 with profitability rate of 33.8 %), while that of strata II was 1.42 and profitability rate of 41.9 %.